The people's choice how the voter makes up his mind in a presidential campaign - Lazarsfeld, Paul Felix 1901-1976; Berelson, Bernard 1912-1979; Gaudet-Erskine, Hazel 1908-1975 (A Columbia paperback, 2019)
Examines how the voter makes up their mind in a presidential election. Also looks at the social and ideological differences between republicans and democrats during the early 1900's and who participates in elections